The influence of external contingency factors and activity-based costing implementation on organizational performance - Albalaki, Faeq Malallah Mahmood; Zarifah Abdullah,; Hasnah Kamardin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Activity-Based Costing (ABC) system continues to gain attention due to the increasing challenges in the current business environment. This situation motivated the researchers to examine external contingency factors (environmental uncertainty (EU) and market orientation (MO)) that influence ABC implementation and the possible effects of ABC implementation on organizational performance. This study also examines the mediating effect of ABC implementation on the relationship between external contingency factors and organizational performance in a developing economy. A cross-sectional survey was conducted among 114 manufacturing companies in Iraq. The data was analyzed using PLS3-SEM, and the results revealed that EU and MO have a positive and significant effect on ABC implementation, and that ABC implementation has a positive and significant effect on organizational performance. Furthermore, this study establishes the mediating role of ABC implementation on the relationship between external contingency factors and organizational performance.